The FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN PASIEN BPJS RAWAT JALAN DALAM PENGAMBILAN OBAT DI FARMASI RSUD H. ABDUL MANAP JAMBI TAHUN 2024 - Alfareza , Rizky Dimas; Afriany , Renny; Lestari, Vina Dwi (Journal of Hospital Administration and Management (JHAM), 2025)
Pharmaceutical services have an important role in supporting the quality of hospital services, especially in increasing patient satisfaction. Pharmaceutical installations are responsible for the supply and distribution of drugs in accordance with regulations. Factors such as drug availability and prescription lead times affect patient satisfaction. A survey at H. Abdul Manap Jambi Hospital showed complaints about the length of waiting time due to limited resources, so an in-depth study is needed related to the factors that affect the satisfaction of outpatient BPJS patients. The purpose of this study is to find out the factors that affect the satisfaction of outpatient BPJS patients in taking drugs at the Pharmaceutical Installation of H. Abdul Manap Jambi Hospital. The approach used was quantitative descriptive with a sample of 100 BPJS patients selected by purposive sampling. The research instrument is in the form of a questionnaire sheet that has been tested for validity and reliability using SPSS 23. The results of the analysis showed that of the 5 (five) factors that affect patient satisfaction, the most were the availability and completeness of drugs. A total of 49 respondents stated that the availability of drugs is the most important factor in determining satisfaction. The conclusion of this study is that the availability and completeness of drugs in pharmaceutical services affect the satisfaction level of outpatient BPJS patients. Based on the research findings, it is therefore necessary to increase the number of pharmacy staff and implement an optimal drug management system to support the improvement and development of patient satisfaction at RSUD H. Abdul Manap Kota Jambi in the future.